Evaluating the accuracy of CEREC intraoral scanners for inlay restorations: impact of adjacent tooth materials - Yeongjun Kwon; Jae-Hoon Kim; Jeong-Kil Park; Sung-Ae Son (BMC, 2024)
Abstract Background The accuracy of intraoral scanning is critical for computer-aided design/computer-aided manufacturing workflows in dentistry. However, data regarding the scanning accuracy of various adjacent restorative materials and intraoral scanners are lacking. This in vitro study aimed to evaluate the effect of adjacent restorative material type and CEREC's intraoral scanners on the accuracy of intraoral digital impressions for inlay cavities. Methods The artificial tooth was prepared with an occlusal cavity depth of 2 mm, a proximal box width at the gingival floor of 1.5 mm, and an equi-gingival margin extended disto-occlusally at the transition line angle on both the lingual and buccal sides for an inlay restoration. The adjacent teeth were veneered with crowns made of gold and zirconia, and an artificial tooth (resin) was utilized as the control group. The inlay cavity and adjacent teeth (Gold, Zirconia, and resin) were scanned 10 times using Chairside Economical Restoration of Esthetic Ceramics (CEREC) Primescan (PS), Omnicam (OC), and Bluecam (BC). A reference scan was obtained using a laboratory scanner (3-shape E3). Scanning was performed according to the manufacturer's instructions, including powder application for the BC group. Standard tesselation language files were analyzed using a three-dimensional analysis software program. Experimental data were analyzed using a two-way analysis of variance and the Tukey's post-hoc comparison test. Results The restorative materials of the adjacent teeth significantly affected the accuracy of the intraoral digital impressions (p < .05). The zirconia group exhibited the highest trueness deviation, followed by the resin and gold groups, with each demonstrating a statistically significant difference (p < .05). The resin group demonstrated the highest maximum positive deviation and deviation in precision. Gold exhibited the lowest average deviation value for trueness compared with those of the other adjacent restorative materials. Intraoral scanner type significantly influenced the trueness and precision of the scan data (p < .05). The average deviation of trueness according to the intraoral scanner type increased in the following order: BC > PS > OC. The average deviation in precision increased in the following order: PS>OC>BC (p < .05). Conclusion The restorative materials of the adjacent tooth and the type of intraoral scanner affect the accuracy of the intraoral digital impression. The trueness of the digital images of the BC group, obtained by spraying the powder, was comparable to that of the PS group. Among the adjacent restorative materials, zirconia exhibited the lowest trueness. In contrast, PS demonstrated the highest precision among the intraoral scanners, while resin displayed the lowest precision among the adjacent restorative materials.